Ciclomobilidade como alternativa para uma cidade mais democrática : uma proposta para Várzea Grande (MT) - Gama, João Victor Cordeiro (2024)
To think about urban mobility in Várzea Grande is to reflect on its history from the production of urban space, since mobility is historically at the heart of the evolution of cities. The current urban configuration of Várzea Grande is linked to the existence of a central road network that, since the beginning of territorial occupation, has played an important role in the mobility of people, flow of goods, and expanded reproduction of capital in the Mato Grosso territory. The existence of this geographical fixture, the geographical situation, and the arrival of modernity (light, bridge construction, transformation of the cattle trail into modern roads, construction of the airport, etc.) contributed to the intensification of spatial interactions over time, impacting the urbanization process. The 1970s marked an important milestone for the intensification of spatial interactions both on a regional and intra-urban scale, with reflections on the urbanization process and the issue of urban mobility. It was from this period that the city “Gateway to the Amazon” received a high migratory flow and financial investments aimed at implementing the industrial park and remodeling the road axes to meet the mobility of capital in space and, consequently, promoting the (im)mobility of people who come to live in an increasingly dispersed and fragmented city. It is inferred that (im)mobility is related to a city model that prioritizes automobility, which, in addition to being harmful to the environment, contributes to exacerbating socio-spatial inequalities and reducing spaces for sociability in the city. In this sense, this work seeks to rethink for Várzea Grande a model of urban mobility that is sustainable, inclusive, safe, and democratic. Cycle mobility is pointed out as a viable modal alternative due to the fact that, in addition to being sustainable, it can contribute to mitigating socio-spatial inequalities, improving quality of life, and ensuring democratic access to the city of Várzea Grande.